2014
DOI: 10.1007/s13762-014-0581-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of aerodynamic sound noise generated by a large-scaled wind turbine and its physiological evaluation

Abstract: Aerodynamic noise generated from a modern large-scale wind turbine was measured and analyzed from an engineering point of view. The measurement items were the sound, the sound pressure level (including the infrasound with extremely low-frequency band) and the corresponding physiological evaluation. Fifteen test subjects received various sound stimuli, including the recorded aerodynamic noise and a synthetic periodical sound, were examined with an electroencephalogram as a physiological evaluation. It was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…A scoping review by Freiberg et al 2018 found "no specific overall health effects of working in the wind sector" but found associations with accident rates which resulted in injuries or fatalities [5]. Other occupational worker research has reported WT noise annoyance and other adverse health effects which are consistent with reports by residents who live near WT [14]- [20].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…A scoping review by Freiberg et al 2018 found "no specific overall health effects of working in the wind sector" but found associations with accident rates which resulted in injuries or fatalities [5]. Other occupational worker research has reported WT noise annoyance and other adverse health effects which are consistent with reports by residents who live near WT [14]- [20].…”
Section: Introductionmentioning
confidence: 83%
“…Since the Health Canada Study design of 2012, methods have evolved. Objective measurements have included the use of advanced methods and technologies such as: a time stratified, case-crossover design [85]; MRI technology to document changes of brain activity when exposed to infrasound from WT [86]; verification of the physiological impact by ECG (electrocardiogram) [20] and brain waves by electroencephalogram (EEG) associated with low frequency/infrasound [87]; and a double blind provocation case control pilot [88].…”
Section: While Researchers Can Comment On Health Canada Study's Intermentioning
confidence: 99%
“…Windmills are also a source of infrasound due to turbulent air flow past its blades and its rotating machinery, where it was found to be an annoyance to technicians working in close proximity to a large-scale wind farm [13]. This is emerging as tangible hazards that could affect a large part of renewable energy generation systems worldwide.…”
Section: Seismicity and Locating Regions Of Infrasound Worldwide Alonmentioning
confidence: 99%
“…In a study reported [53] from Japan, 15 subjects were experimentally exposed A. Evans to various sound stimuli, including recorded aerodynamic noise and Infrasound, along with synthetic periodic sound, and were evaluated by electroencephalography. The induced rate of alpha1 rhythm decreased when the test subjects listened to all the sound stimuli and decreased further with reducing frequency.…”
Section: A Evansmentioning
confidence: 99%